RETRACTED: Synergistic development of intangible cultural heritage and tourism industry: Empirical experiences from Jilin, China - Jing Lv; Yuanlu Chai; Xinyue Hu (PLoS ONE, 2025)
This study focuses on the Jilin region of China, conducting a multidimensional assessment of the current state of the synergistic development between Intangible Cultural Heritage (ICH) and the tourism industry in the area. The objective is to explore the issues surrounding the coordinated development of ICH and the tourism sector. The findings are as follows: 1) The overall coupling degree between the ICH and tourism systems in the Jilin region is 0.7851, with 91.99% of the indicators falling within the high correlation range and 8.01% within the very high correlation range, indicating a strong coupling effect between the two systems; 2) Structural coupling analysis shows that the coupling degree is highest in Changchun City and weakest in Baicheng City. In Changchun, the proportions of indicators in Quadrant I (maintain current status) are 50%, 50%, and 54.84%, respectively, while in Baicheng, the proportions in Quadrant II (priority improvement) reach 50%, 63.5%, and 47.5%, respectively; 3) Dynamic coupling analysis reveals that from 2008 to 2022, the ICH and tourism systems in the Jilin region exhibited a trend of coordinated development. This study not only confirms the synergistic relationship between ICH and the tourism industry, enriching theoretical research in this field, but also provides practical guidance for other regions seeking to achieve coordinated development between ICH and tourism, thereby holding significant practical value.